THE IMPORTANCE OF THE SCHWYZ BREED OF CATTLE IN IMMUNOGENESIS AND CELLETION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Describes the work and solutions related to determining the immunogenetic characteristics of cattle brought from Switzerland and the possibilities of their use in breeding, which are kept in a number of regions of our repub.